2018
DOI: 10.1371/journal.pgen.1007292
|View full text |Cite
|
Sign up to set email alerts
|

Sequential induction of three recombination directionality factors directs assembly of tripartite integrative and conjugative elements

Abstract: Tripartite integrative and conjugative elements (ICE3) are a novel form of ICE that exist as three separate DNA regions integrated within the genomes of Mesorhizobium spp. Prior to conjugative transfer the three ICE3 regions of M. ciceri WSM1271 ICEMcSym1271 combine and excise to form a single circular element. This assembly requires three coordinated recombination events involving three site-specific recombinases IntS, IntG and IntM. Here, we demonstrate that three excisionases–or recombination directionality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…Under certain conditions, GIs can be excised from the chromosome through the site-specific recombination between the direct repeated sequences (DRSs) that flank the element, in a reaction catalyzed by the integrase protein encoded within or outside the island [80][81][82][83]. This reaction, which is usually promoted by a recombination directionality factor also encoded inside or outside the GI, results in the formation of a circular element [84,85]. The insertion site is reconstituted in the chromosome, and a copy remains as part of the excised GI.…”
Section: Genomic Islandsmentioning
confidence: 99%
“…Under certain conditions, GIs can be excised from the chromosome through the site-specific recombination between the direct repeated sequences (DRSs) that flank the element, in a reaction catalyzed by the integrase protein encoded within or outside the island [80][81][82][83]. This reaction, which is usually promoted by a recombination directionality factor also encoded inside or outside the GI, results in the formation of a circular element [84,85]. The insertion site is reconstituted in the chromosome, and a copy remains as part of the excised GI.…”
Section: Genomic Islandsmentioning
confidence: 99%
“…Here, we will focus on the role of QS on relevant traits such as EPS production and motility and we will discuss the relevance of this regulatory system in the establishment of symbiosis. For information about QS-controlled transfer of plasmids and symbiosis islands, readers are referred to more detailed studies [ 69 , 77 , 83 , 87 , 92 , 93 , 94 ].…”
Section: Functions Regulated By Quorum Sensing In Rhizobiamentioning
confidence: 99%
“…We have previously demonstrated that a synthetic "mini-ICE" carrying only intS and attP integrates into the phe-tRNA gene in R7ANS; a derivative of R7A from which ICEMlSym R7A was cured (20). The ICEMlSym R7A RDF, RdfS, is a putative member of the MerR superfamily of winged helixturn-helix (wHTH) DNA-binding proteins (12,33,34 (20). Escherichia coli DC10B (41) cultures were grown in Lysogeny broth (LB) at 37⁰C.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…1). rdfS is the first gene in a polycistronic operon encoding traF, msi107 and probably rlxS (33,58). The traF start site also overlaps with the rdfS stop codon suggesting they may be translationally coupled.…”
Section: Accepted Manuscriptmentioning
confidence: 99%